Motivational Profiles: The Role of Personal and Contextual Variables - Thamir Danir Durán Fonseca; Guadalupe Acle Tomasini (Universidad Autónoma de Baja California, 2022)
The objectives of the study were to identify and describe motivational profiles in elementary students based on personal variables, namely school motivation, task value, and academic self-concept; and to describe the contextual variables of parental and teacher support in students with different profiles. In a mixed-methods study, 248 students completed various questionnaires relating to the variables, and then six tutors and six teachers were interviewed to determine their involvement. Quantitative data was analyzed through clustering and MANOVA, and categorical content analysis was used for qualitative information. The results showed significant differences in the three profiles: high, moderate, and low. The mothers of highly motivated children are more involved in their children's academic activities, and their teachers demonstrate greater recognition and are more dynamic in teaching.